Monitoring STI prevalence using telephone surveys and mailed urine specimens: a pilot test. Issue 3 (27th May 2005) - Eggleston, E; Turner, C F; Rogers, S M; Roman, A; Miller, W C; Villarroel, M A; Ganapathi, L
Abstract : Objectives: This pilot test assessed the feasibility of a cost effective population based approach to STI monitoring using automated telephone interviews, urine specimen collection kits sent out and returned by US Postal Service mail, and monetary incentives to motivate participation. Methods: 100 residents of Baltimore, MD, USA, completed an automated telephone survey and agreed to mail in a urine specimen to be tested for chlamydia and gonorrhoea. Participants were paid $10 for completing the survey and $40 for mailing the specimen. Results: 86% of survey participants mailed in a urine specimen for testing. Conclusions: Automated telephone surveys linked with testing of mailed-in urine specimens may be a feasible lower cost (relative to household surveys) method of estimating infection prevalences in a population.